Targeted Pten deletion plus p53-R270H mutation in mouse mammary epithelium induces aggressive claudin-low and basal-like breast cancer. Issue 1 (December 2016) - Wang, Sharon; Liu, Jeff; Kim, Danbi; Datti, Alessandro; Zacksenhaus, Eldad
Abstract Background Triple-negative breast cancer (TNBC), an aggressive disease comprising several subtypes including basal-like and claudin-low, involves frequent deletions or point mutations in TP53, as well as loss of PTEN. We previously showed that combined deletion of both tumor suppressors in the mouse mammary epithelium invariably induced claudin-low-like TNBC. The effect of p53 mutation plus Pten deletion on mammary tumorigenesis and whether this combination can induce basal-like TNBC in the mouse are unknown. Methods WAP-Cre:Ptenf/f :p53lox.stop.lox_R270H composite mice were generated in which Pten is deleted and a p53-R270H mutation in the DNA-binding domain is induced upon expression of Cre-recombinase in pregnancy-identified alveolar progenitors. Tumors were characterized by histology, marker analysis, transcriptional profiling [GEO-GSE75989], bioinformatics, high-throughput (HTP) FDA drug screen as well as orthotopic injection to quantify tumor-initiating cells (TICs) and tail vein injection to identify lung metastasis. Results Combined Pten deletion plus induction of p53-R270H mutation accelerated formation of four distinct mammary tumors including poorly differentiated adenocarcinoma (PDA) and spindle/mesenchymal-like lesions. Transplantation assays revealed highest frequency of TICs in PDA and spindle tumors compared with other subtypes. Hierarchical clustering demonstrated that the PDA and spindle tumors grouped closely with human as well as mouse models of basal and claudin-low subtypes, respectively. HTP screens of primary Pten∆ :p53∆ vs. Pten∆ :p53R270H spindle tumor cells with 1120 FDA-approved drugs identified 8-azaguanine as most potent for both tumor types, but found no allele-specific inhibitor. A gene set enrichment analysis revealed increased expression of a metastasis pathway in Pten∆ :p53R270H vs. Pten∆ :p53∆ spindle tumors. Accordingly, following tail vein injection, both Pten∆ :p53R270H spindle and PDA tumor cells induced lung metastases and morbidity significantly faster than Pten∆ :p53∆ double-deletion cells, and this was associated with the ability of Pten∆ :p53R270H tumor cells to upregulate E-cadherin expression in lung metastases. Conclusions Our results demonstrate that WAP-Cre:Ptenf/f :p53lox.stop.lox_R270H mice represent a tractable model to study basal-like breast cancer because unlike p53 deletion, p53R270H mutation in the mouse does not skew tumors toward the claudin-low subtype. The WAP-Cre:Ptenf/f :p53lox.stop.lox_R270H mice develop basal-like breast cancer that is enriched in TICs, can readily form lung metastasis, and provides a preclinical model to study both basal-like and claudin-low TNBC in immune-competent mice.